A Statistical Survey of Leukemia in Ontario and at the Ontario Cancer Foundation Clinics, 1938-1958 - MacKay, E. N. (1967)
In Ontario, leukemia causes about 4% of all cancer deaths, ranging from nearly 50% at under 5 years of age to 1-3% at age 50 and over. Age-specific death rates are highest among older people; at all ages, male deaths exceed female deaths. Only about 20% of all leukemia patients in Ontario are registered at Ontario Cancer Clinics; the proportion changed sharply with the advent of chemotherapy. For 1258 patients registered in 1938-1963, the crude one-year survival rate was 50%, ranging from 9% for acute leukemia to about 60% for non-acute lymphatic and myeloid leukemia. The long-term outlook was much better for non-acute lymphatic leukemia than for non-acute myeloid leukemia. For acute leukemia, the treatment of choice was chemotherapy; for non-acute lymphatic leukemia, radiotherapy was used, followed, if required, by chemotherapy or further radiotherapy. For non-acute myeloid leukemia, the advantage of chemotherapy over radiotherapy was not established.